1997
DOI: 10.1023/a:1005878622437
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Benzoyl-CoA:anthranilate N-benzoyltransferase catalyzes the first committed reaction of phytoalexin biosynthesis in carnation (Dianthus caryophyllus L.), and the product N-benzoylanthranilate is the precursor of several sets of dianthramides. The transferase activity is constitutively expressed in suspension-cultured carnation cells and can be rapidly induced by the addition of yeast extract. The enzyme was purified to homogeneity from yeast-induced carnation cells and shown to consist of a single polypeptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(44 citation statements)
references
References 23 publications
3
41
0
Order By: Relevance
“…Biosynthetic analysis using Taxus brevifolia mature bark tissue as enzyme source demonstrated that N-benzoylation of 3Ј-debenzoyltaxol is the final step in the Taxol pathway (4). The substantial deduced sequence identity (58-69%) within a family of nine cloned acyltransferases from Taxus (10) [including a taxoid 2-O-benzoyltransferase among the three which have been functionally defined (17)] and between these and a Dianthus anthranilate N-hydroxycinnamoyl͞benzoyltrans-ferase (Ϸ50-57%) (18) suggested that one of the six remaining undefined Taxus clones might encode the N-debenzoyltaxol N-benzoyltransferase.…”
Section: Resultsmentioning
confidence: 99%
“…Biosynthetic analysis using Taxus brevifolia mature bark tissue as enzyme source demonstrated that N-benzoylation of 3Ј-debenzoyltaxol is the final step in the Taxol pathway (4). The substantial deduced sequence identity (58-69%) within a family of nine cloned acyltransferases from Taxus (10) [including a taxoid 2-O-benzoyltransferase among the three which have been functionally defined (17)] and between these and a Dianthus anthranilate N-hydroxycinnamoyl͞benzoyltrans-ferase (Ϸ50-57%) (18) suggested that one of the six remaining undefined Taxus clones might encode the N-debenzoyltaxol N-benzoyltransferase.…”
Section: Resultsmentioning
confidence: 99%
“…C. breweri BZL catalyzes the thioesterification of benzoic acid to its corresponding CoA derivative. There are multiple examples in plant secondary metabolism that feature benzoic acid as a biosynthetic building block [1][2][3][4]. Benzoylation of these compounds is catalyzed by acyltransferases that require benzoyl-CoA as a substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Benzoic acid is a component of many secondary metabolites in plants, including cocaine [1], taxol [2], dianthramide B [3], and some glucosinolates [4]. In these and other molecules, the benzoyl moiety is transferred by acyltransferases, requiring activated benzoyl-CoA as a substrate.…”
mentioning
confidence: 99%
“…The radioactivity present on the TLC plates was localized and quantitated with a Rita Star TLC scanner (Raytest). The identity of the enzymic reaction product as thebaine was ascertained by HPLC-MS using a Finnigan MAT TSQ 7000 (electrospray voltage, 4.5 kV; capillary temperature, 220°C; carrier gas, N 2 ) coupled to a Micro-Tech Ultra-Plus Micro-LC equipped with an Ultrasep RP18 column ( (22); BEAT, benzylalcohol acetyltransferase from C. breweri (26), HCBT, anthranilate N-hydroxycinnamoyl/benzoyltransferase from D. caryophyllus (27); DBAT, 10-deacetylbaccatin III-10-O-acetyltransferase and TAT, taxadienol acetyltransferase, both from T. cuspidata (28,29). Black boxes indicate conserved residues; white boxes indicate the internal peptide sequences obtained from native salutaridinol 7-O-acetyltransferase; arrows indicate the positions of the peptides used to design oligodeoxynucleotide primers for RT-PCR; # denotes positions of the highly conserved consensus sequence HXXXD.…”
Section: Figmentioning
confidence: 99%
“…E, HPLC-positive ion electrospray mass spectral analysis of thebaine standard. alcohol acetyltransferase from Clarkia breweri (34%) (26), anthranilate N-hydroxycinnamoyl/benzoyltransferase from Dianthus caryophyllus (25%) (27), taxadienol acetyltransferase (24%), and 10-deacetylbaccatin III-10-O-acetyltransferase (22%) both from Taxus cuspidata (28,29).…”
Section: (Fvfdfak) 5ј-tt(t/c) Gt(g/a/t) Tt(t/c) Ga(c/t) Tt(t/c) Gc(amentioning
confidence: 99%